2019
DOI: 10.1590/2175-8239-jbn-2018-0171
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and volume status evaluation of hemodialysis patients with and without residual renal function in the long interdialytic interval

Abstract: Introduction: It is unclear whether residual renal function (RRF) in dialysis patients can attenuate the metabolic impact of the long 68-hour interdialytic interval, in which water, acid, and electrolyte accumulation occurs. Objective: to evaluate serum electrolyte levels, water balance, and acid-base status in dialytic patients with and without RRF over the long interdialytic interval (LII). Methodology: this was a single-center, cross-sectional, and analytical study that compared patients with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Ma and Ding 24 showed that patients with RUO had lower serum phosphate and parathormone levels while maintaining higher serum calcium levels. In their study Almeida et al 29 also showed that patients with RRF have lower phosphatemia values. Moreover, they presented that the group without RRF had significantly higher potassium levels increase during the long interdialytic interval.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Ma and Ding 24 showed that patients with RUO had lower serum phosphate and parathormone levels while maintaining higher serum calcium levels. In their study Almeida et al 29 also showed that patients with RRF have lower phosphatemia values. Moreover, they presented that the group without RRF had significantly higher potassium levels increase during the long interdialytic interval.…”
Section: Discussionmentioning
confidence: 87%
“…Those patients also exhibited lower sodium levels, and a greater percentage of patients with natremia below 137 mmol/l was present in the anuric group. Almedia et al 29 also suggested that patients without RRF are more likely to have lower bicarbonate levels and inadequate respiratory response to metabolic acidosis. These patients also showed higher interdialytic weight gain, which could be an explanation for the inadequate respiratory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study carried out in the North East of Brazil, showed that patients with decreased RRF had an average of two years of haemodialysis, and those who did not have it were on treatment for an average of 7.2 years. Also, in this study, whereby patients with and without RRF were compared, it was found that patients without RRF had a greater intradialytic weight gain 25 .…”
Section: Such Diagnoses Signify Priority Nursing Attentionmentioning
confidence: 68%
“…This is lower than the postdialysis means of 3.7 mEq/L and 4.1 mEq/L reported previously after the last dialysis of the week. 5,6 However, postdialysis hypokalemia by itself is not associated with higher mortality when statistical adjustments are made for the older age and greater morbidity characterizing this group. 4 This might be explained by the rapid rebound of serum potassium levels due to movement of potassium from cells to the extracellular fluid, which corrects postdialysis hypokalemia to or close to normal within 5 hours.…”
mentioning
confidence: 99%